From tryptamine to the discovery of efficient multi-target directed ligands against cholinesterase-associated neurodegenerative disorders - Wu, Junbo; Zhang, Honghua; Wang, Yuying; Yin, Gaofeng; Li, Qien; Zhuo, Linsheng; Chen, Hongjin; Wang, Zhen (Frontiers in Pharmacology, 2022)
A novel class of benzyl-free and benzyl-substituted carbamylating tryptamine derivatives (CDTs) was designed and synthesized to serve as effective building blocks for the development of novel multi-target directed ligands (MTDLs) for the treatment of neurological disorders linked to cholinesterase (ChE) activity. The majority of them endowed butyrylcholinesterase (BuChE) with more substantial inhibition potency than acetylcholinesterase (AChE), according to the full study of ChE inhibition. Particularly, hybrids with dibenzyl groups (2b-2f, 2j, 2o, and 2q) shown weak or no neuronal toxicity and hepatotoxicity and single-digit nanomolar inhibitory effects against BuChE. Through molecular docking analysis and kinetic analysis, the potential mechanism of action on BuChE was first investigated. In vitro H2O2-induced HT-22 cells assay demonstrated the favorable neuroprotective potency of 2g, 2h, 2j, 2m, 2o and 2p. Besides, 2g, 2h, 2j, 2m, 2o and 2p also endowed good antioxidant activities and COX-2 inhibitory effects. This study suggested that this series of hybrids can be applied for the treatment of various ChE-associated neurodegenerative disorders such as Alzheimer’s disease and Parkinson's disease, as well as promising building blocks for the further structure modification to develop efficient MTDLs.